Development Of Erp And Dashboard On Module Accounting Using The Economy Circular Concept In The Msme Industry - Wardana, Bimo Rahmatillah; Ridwan, Ari Yanuar; Hediyanto, Umar Yunan Kurniawan Septo (eProceedings of Engineering, 2024)
Abstract — This research paper aims to develop an ERPsystem and a customized dashboard with software Odoo as maindriver for the accounting module, integrating CircularEconomy principles, specifically for the MSME leather tanningindustry. The focus is on enhancing operational efficiency,sustainability, and resource optimization within the sector. Thestudy adopts quickstart approach on developing ERPaccounting system. Leveraging Circular Economy insights, theERP system will promote sustainable sourcing, waste reduction,and product lifecycle extension. The customized dashboard willoffer real-time financial data for informed decision-making,tracking circularity metrics, and improving strategic choices. Keywords— ERP system, Odoo, Accounting module,Circular Economy principles, MSME, leather tanning industry.